การพัฒนารูปแบบการจัดการเรียนรวมแบบคละชั้นที่มีเด็กที่มีความต้องการพิเศษในโรงเรียนประถมศึกษา (A DEVELOPMENT OF MULTILEVEL INCLUSIVE EDUCATION FOR STUDENTS WITH SPECIAL NEEDS IN PRIMARY SCHOOLS) - ส่งเสริม กิ่งเพชร; อารยะวิญญู ผดุง (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2015)
บทคัดย่อ การศึกษาครั้งนี้มีความมุ่งหมายเพื่อสร้างรูปแบบ ศึกษาประสิทธิผลของรูปแบบและประเมินความเหมาะสมของรูปแบบการจัดการเรียนรวมแบบคละชั้นที่มีเด็กที่มีความต้องการพิเศษในโรงเรียนประถมศึกษา กลุ่มตัวอย่างที่เป็นกลุ่มทดลอง ได้แก่ นักเรียนชั้นประถมศึกษาปีที่ 1-3 โรงเรียนบ้านโพธิ์ อำเภอสังขะ จังหวัดสุรินทร์ จำนวน 31 คน กลุ่มควบคุม ได้แก่ นักเรียนชั้นประถมศึกษาปีที่ 1-3 โรงเรียนบ้านระไซร์ (เด่นพัฒนา) อำเภอเมือง จังหวัดสุรินทร์ จำนวน 19 คน เครื่องมือที่ใช้ในการวิจัย ได้แก่ แบบประเมินความสอดคล้องของรูปแบบ แบบทดสอบวัดผลสัมฤทธิ์ทางการเรียน แบบประเมินความพึงพอใจต่อรูปแบบของครู ผู้บริหาร นักเรียนและผู้ปกครอง แบบประเมินความเหมาะสมของรูปแบบโดยผู้ทรงคุณวุฒิ ผลการวิจัยพบว่า 1) มีความแตกต่างระหว่างค่าเฉลี่ยของคะแนนผลสัมฤทธิ์ทางการเรียนก่อนและหลังการทดลองและระหว่างกลุ่มทดลองและกลุ่มควบคุมที่เป็นเด็กปกติและเด็กที่มีความต้องการพิเศษ 2) นักเรียนกลุ่มทดลองที่เป็นเด็กปกติและเด็กที่มีความต้องการพิเศษมีคะแนนผลสัมฤทธิ์ทางการเรียนหลังการทดลองเมื่อเทียบกับเกณฑ์มีผลการเรียนอยู่ในระดับดี 3) นักเรียนกลุ่มควบคุมที่เป็นเด็กปกติมีคะแนนผลสัมฤทธิ์ทางการเรียนหลังการทดลองเมื่อเทียบกับเกณฑ์มีผลการเรียนอยู่ในระดับดี สำหรับเด็กที่มีความต้องการพิเศษมีคะแนนผลสัมฤทธิ์ทางการเรียนหลังการทดลองเมื่อเทียบกับเกณฑ์มีผลการเรียนอยู่ในระดับต่ำกว่าเกณฑ์ 4) ครู ผู้บริหาร นักเรียนและผู้ปกครอง มีความพึงพอใจต่อรูปแบบในแต่ละด้านและรวมอยู่ในระดับมาก 5) ผู้ทรงคุณวุฒิประเมินความเหมาะสมของรูปแบบทุกข้อความและรวมมีความเหมาะสมมากที่สุด Abstract The objectives of this study were to develop models, to examine effectiveness, and to assess the suitability of the models of multilevel inclusive education for students with special needs in primary schools. The experimental group was comprised of 31 students in Grade 1-3, Ban Pho School, Sang Kha District, Surin, whereas the control group was the students in Grade 1-3, Ban Rasai (Den Pattana) School, Muang District, Surin. Research tools were the consistency of models test, the achievement test, the model satisfaction test, evaluated by teachers, administrators, students and students’ parents, and the model suitability test evaluated by honorable members. The research findings were as follows. 1) The difference in the average point of the achievement of both pre and post experiment, and the difference in the average point of achievement of both the experimental group and the control group. 2) The experimental group who has been normal students and students with special needs have achieved their study achievement in the post experiment, compared to the criteria, at the good level. 3) The control group who has been normal students achieved their study achievement in the post experiment, compared to the criteria, at the good level. While the students with special needs have achieved their study achievement in the post experiment under the criteria. 4) The satisfaction assessment towards the models was evaluated by teachers, administrators, students and students’ parents, and it was found that they satisfied of the models in both individual and overall aspects at the high level. 5) The suitability assessment towards the models was evaluated by honorable members who assessed that the models were suitable in both every context, and indicated that the overall models were at the highest degree.